Prognostic impact of clinical variables on surgically resected small-cell lung cancer: Results of a retrospective multicenter analysis (FIGHT002A and HOT1301A). Issue 3 (December 2015) - Yokouchi, Hiroshi; Ishida, Takashi; Yamazaki, Shigeo; Kikuchi, Hajime; Oizumi, Satoshi; Uramoto, Hidetaka; Tanaka, Fumihiro; Harada, Masao; Akie, Kenji; Sugaya, Fumiko; Fujita, Yuka; Fukuhara, Tatsuro; et al.
Highlights: We examined prognostic impact of clinical variables on surgically resected SCLC. Overall survival (OS) was longer in patients at c-stage I and II. The results partly supported the ESMO guidelines for early-stage SCLC. Abstract: Objectives: Several American and Japanese guidelines recommend surgery for patients with c-stage I small-cell lung cancer (SCLC), whereas the European Society of Medical Oncology (ESMO) guidelines recommend surgery for patients with not only c-stage I but also c-stage II (T2N1) SCLC. In addition, previous studies identified various factors other than clinical stage that are related to survival in these patients. Thus, further validation and examination of the association of clinical stage and other clinical variables with survival are required for establishing practical management of early-stage SCLC. Patients and methods: We reviewed the clinical courses of 156 SCLC patients who had undergone surgery at 17 institutions between January 2003 and January 2013. Results: Clinical stages (tumor-node-metastasis [TNM] version 7) of the 156 patients were 98 cases in IA, 14 in IB, 16 in IIA, 7 in IIB, 18 in IIIA, and 3 in IIIB. Median overall survival (OS) was 33.3 months (95% confidence interval: 20.9–45.8). Multivariate analysis revealed that OS was longer in patients either at c-stage II and under, with a maximum tumor diameter of <20 mm, with preoperative diagnosis, without a history or presence of other types of cancer, or who underwent prophylactic cranial irradiation (PCI). Conclusion: These results indicate that a history or presence of other types of cancer might be a major decisive factor for surgery. Patients with c-stages I and II (c-T2N1) can be considered for surgery, and PCI may be useful in patients undergoing surgery in a practical setting, partly supporting the ESMO guidelines. 1